Middle meningeal artery embolization for chronic subdural hematoma: a systematic review - Omura, Yoshihiro; Ishiguro, Taichi (Frontiers in Neurology, 2023)
Background Chronic subdural hematoma (cSDH) is one of the most common diseases in neurosurgery. Middle meningeal artery embolization (MMAE) is reportedly an option to prevent recurrence or avoid surgery in patients with cSDH. This study was performed to review the evidence on MMAE for cSDH and evaluate its safety, efficacy, indications, and feasibility. Methods We systematically reviewed the literature according to the PRISMA guidelines using an electronic database. The search yielded 43 articles involving 2,783 patients who underwent MMAE. Results The hematoma resolution, recurrence, and retreatment rates in the MMAE-alone treatment group (n = 815) were 86.7%, 6.3%, and 9.6%, respectively, whereas those in the prophylactic MMAE with combined surgery group (n = 370) were 95.6%, 4.4%, and 3.4%, respectively. The overall MMAE-related complication rate was 2.3%. Conclusion This study shows that MMAE alone is, although not immediate, as effective as evacuation surgery alone in reducing hematoma. The study also shows that combined treatment has a lower recurrence rate than evacuation surgery alone. Because MMAE is a safe procedure, it should be considered for patients with cSDH, especially those with a high risk of recurrence.